Reduced acoustic and electric integration in concurrent-vowel recognition - Yang, Hsin-I; Zeng, Fan-Gang (Scientific reports, 2013)
The present study used concurrent-vowel recognition to measure integration efficiency of combined acoustic and electric stimulation in eight actual cochlear-implant subjects who had normal or residual low-frequency acoustic hearing contralaterally. Although these subjects could recognize single vowels (>90% correct) with either electric or combined stimulation, their performance degraded significantly in concurrent-vowel recognition. Compared with previous simulation results using normal-hearing subjects, the present subjects produced similar performance with acoustic or electric stimulation alone, but significantly lower performance with combined stimulation. A probabilistic model found reduced integration efficiency between acoustic and electric stimulation in the present subjects. The integration efficiency was negatively correlated with residual acoustic hearing in the non-implanted ear and duration of deafness in the implanted ear. The present result suggests a central origin of the integration deficit and that this integration be evaluated and considered in future management of hearing impairment and design of auditory prostheses.